Comparison of Electron Transfer Properties of the SEI on Graphite Composite and Metallic Lithium Electrodes by SECM at OCP. Issue 13 (1st January 2015) - Bülter, H.; Peters, F.; Schwenzel, J.; Wittstock, G.
Abstract : The passivating properties of solid electrolyte interphases (SEI) at metallic lithium were characterized using the feedback mode of scanning electrochemical microscopy (SECM) and 2, 5-di- tert -butyl-1, 4-dimethoxybenzene (DBDMB) as redox mediator at OCP. The SEI at Li allows electron transfer toward DBDMB with finite rate. In comparison to charged graphite composite electrodes, the electron transfer rate tends to be smaller at Li. Both, graphite composite and Li electrodes, show a local variation of electron transfer rates and temporal changes within a time span of hours. The long-term changes of SEI passivity at metallic Li are dependent on the solvents in the liquid electrolyte. In addition, significant short-term changes of SEI passivity occur at both electrodes. However, the frequency of such events is smaller for metallic Li compared to graphite. A strong decrease of SEI passivity and a strong increase of fluctuations in the passivating properties are observed when the microelectrode mechanically touches the metallic Li and damages the SEI. The changes of SEI passivity by a mechanical touch are orders of magnitude larger compared to spontaneous changes. A local SEI damage by the microelectrode decreases not only the SEI passivity locally, but also a few hundreds of μm apart.